Leisure Time Management and its Impact on International Tourism Development - Asst. Prof. Dr. Radhi Hammoud Jassim (Peerian Journals Publishing, 2023)
Scientific and technological progress in middle of last century and beginning of the current century has led to a great development in various fields of life, especially economic and social, which has directed to a significant increase in leisure time for many societies, and thus the need for recreation and going outside framework of daily work, psychological stress and requirements of daily life has expanded. Therefore, specialists have been developing tourism and recreational programs that help an individual and the group to invest well, not their free time, so a new philosophy has emerged that is concerned with recreational activities and investment of leisure time. They also have invested this feature and began to develop plans and programs that are consistent with all age groups of tourists to form for them. It is a distinct attraction and gives them AN opportunity to practice all different activities in order to raise morale, build a balanced personality, and move away from routine and the state of anxiety and depression that people suffer from.
Keywords: Leisure time management; tourism sector; inbound international tourism